Investigating associations between social determinants, self-efficacy measurement of sleep apnea and CPAP adherence: the SEMSA study - Gentina, Thibaut; Gentina, Elodie; Douay, Bernard; Micoulaud-Franchi, Jean-Arthur; Pépin, Jean-Louis; Bailly, Sébastien (Frontiers in Neurology, 2023)
Study objectives The prospective Self-Efficacy Measure for Sleep Apnea study (SEMSAS) is investigating thresholds for health literacy, self-efficacy and precariousness at obstructive sleep apnea (OSA) diagnosis to predict CPAP adherence. This paper describes the study protocol and presents baseline data from the ongoing study. Methods Eligible individuals had confirmed OSA and were referred to a homecare provider for continuous positive airway pressure (CPAP) therapy initiation. Data on patient characteristics and comorbidities were collected, along with baseline evaluations of self-efficacy [15-item Self-Efficacy Measure for Sleep Apnea tool (SEMSA-15)], precariousness [Deprivation in Primary Care Questionnaire (DipCareQ)], and health literacy (Health Literacy Questionnaire). CPAP adherence over 12 months of follow-up will be determined using remote monitoring of CPAP device data. The primary objective is to define an optimal SEMSA-15 score threshold to predict CPAP adherence at 3- and 12-month follow-up. Results Enrollment of 302 participants (71% male, median age 55 years, median body mass index 31.6 kg/m2) is complete. Low self-efficacy (SEMSA-15 score ≤ 2.78) was found in 93/302 participants (31%), and 38 (12.6%) reported precariousness (DipCareQ score > 1); precariousness did not differ significantly between individuals with a SEMSA-15 score ≤ 2.78 versus >2.78. Health literacy was generally good, but was significantly lower in individuals with versus without precariousness, and with low versus high self-efficacy. Conclusion SEMSAS is the first study using multidimensional baseline assessment of self-efficacy, health literacy and precariousness, plus other characteristics, to determine future adherence to CPAP, including CPAP adherence trajectories. Collection of follow-up data is underway.